Tensile and flexural properties of kenaf reinforced polylactic acid under heat effect - Rozli Zulkifli; Meor Syazalee Meor Sha (Penerbit Universiti Kebangsaan Malaysia, 2023)
Biocomposite is a combination of natural reinforcement and natural matrix material consisting of kenaf reinforced with polylactic acid (PLA), where its mechanical properties will be affected when exposed to heat. This research investigates the effect of exposure of biocomposites to different temperatures on the mechanical properties of biocomposites, consisting of tensile and flexural properties. Before producing the sample, kenaf in the form of one-way yarn is conditioned with 40% RH humidity, and then the sample is produced using hot compression molding techniques by combining kenaf with PLA. Tensile and bending tests carried out in a heating chamber with the heat were studied using a Universal Testing Machine (UTM). The choice of heat temperature depends on the glass transition temperature of polylactic acid, where the study temperature ranges from 25 oC to 65 oC. From the results of the study, it was found that the maximum bending strength and modulus (117 MPa, 5.8 GPa) and the maximum tensile strength and modulus (59 MPa, 3.2 GPa) were both obtained at low temperatures (25 oC). While the modulus value decreases significantly at 55 oC, the tensile and flexural properties both show a steady decrease with increasing temperature. Therefore, the presence of temperature has a significant effect on the tensile and flexural properties of kenaf-reinforced PLA biocomposites. When it is exposed to high temperatures, the mechanical quality deteriorates, and the risk of failure increases. Failure is caused by poor reinforcement and matrix bonding caused by the degradation of natural fiber properties of kenaf and the level of PLA plastic deformation.